The origin of Daulah Islamiah Raya with special reference to ideology - Santarita, Joefe B. (Danyag : Journal of Humanities and Social Sciences, 2004)
Daulah Islamiah Raya (DIR) as a concept only gained a significant attention lately when one of its proponents, Jema'ah Islamiah, declared openly its association with al-Qaeda and the series of terrorist activities in Southeast Asia after the 9/11 bombing. This ideal was a response to the call of resurrecting a great Islamic Universal Brotherhood. It traced its development at the turn of the 20th century and subsequently served as the ultimate inspiration of a longer but vigorous libertarian struggles ranging from pan-Islamic to pre-independent movements in Indonesia. This is even supported by the historical claim of the glory formerly enjoyed by the 15th Century mandala. Thus, this narrative fervently hopes to respond to the hypocritical attitude towards Islam specifically, DIR by concentrating in its ideological and historical foundation. At the same time, this article proposes that the ideal will be positively utilized as a pattern to develop a realm, similar to the triangle growth areas in Asia that is economically driven but ideologically anchored on Islam as the primal difference.